EFFECT OF E-171 ON THE MORPHOFUNCTIONAL STATE OF THE ADRENAL GLAND OF SQUID - Nazarova M.E (Western European Studies, 2025)
In the adrenal gland, the food additive E-171 accumulates and negatively affects the rat organism.As a result of this, metabolite changes are observed within the entire organ system.Of food e-171, which is considered a feed additive to the additive to improve its efficiency, quality and stability, causes irreversible changes for the rat organism
Keywords: oziq ovqat qo’shimchalari; titan dioksid; ta’sir spektori